Contribution to development of software system for automatic design of gear boxes for machine tools - Kragujević, Vladimir; Gatalo, Ratko (Journal of Production Engineering, 1989)
This paper presents basic information about a software system for the automatic design of gearboxes for machine tools, which is under development at the Institute for Production Engineering, FTN Novi Sad. Currently, a part of the system related to the design of the gear box’s kinematic structure has been developed. In addition to information about the system’s concepts, this paper provides general information about the module for designing main characteristics and more detailed information about the module for the design of the main gear box kinematic structure.